Intraperitoneal nebulization of ropivacaine for control of pain after laparoscopic cholecystectomy -A randomized control trial - Sai Sandhya; Nitu Puthenveettil; K Vinodan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Use of high dose opioids following laparoscopic surgery delays discharge from the hospital. Unlike intraperitoneal instillation, nebulization has been reported to provide a homogeneous spread of local anesthetics and provide better analgesia. In our study, we aimed to assess the efficacy of intraperitoneal nebulization of local anesthetic in alleviating postoperative pain in patients undergoing laparoscopic cholecystectomy. Material and Methods: This randomized control double-blinded study was conducted after obtaining approval from the hospital ethics committee and informed consent from patients undergoing laparoscopic cholecystectomy under general anesthesia. Patients recruited were divided into two equal groups of 20 each. Group B received intraperitoneal nebulization with 4 ml of 0.75% ropivacaine and Group C received intraperitoneal nebulization with 4ml of saline before surgical dissection. Postoperative pain score using a numeric rating scale was monitored until 24 h, the need for rescue analgesics and associated complications were noted. Chi-square test, Student's test, and Mann-Whitney U test were used for statistical analysis. Results: The pain score was significantly less in Group B during rest and deep breathing up to 24 h with a P value <0.05. The pain score on movement was also less in Group B and this difference was statistically significant at 6 and 24 h (P = 0.004 and 0.005, respectively). Tramadol consumption was less in Group B and was statistically significant at 24 h with P value of 0.044. No adverse events were noted. Conclusion: Intraperitoneal nebulization of ropivacaine is effective and safe in providing postoperative analgesia in patients undergoing laparoscopic cholecystectomy.